Kristina Kappelin, Berlusconi – Italienaren (Stockholm: Brombergs, 2010) - Monica Quirico (Nordicum-Mediterraneum, 2012)
From the point of view of an Italian reader – particularly if female – the book in ten chapters by the Swedish journalist Kristina Kappelin (who has been living in Rome for many years and works as correspondent from Italy for Swedish media) is perhaps interesting more because of what it shows about Sweden than because of what it tells about Berlusconi’s political career. The latter, nevertheless, is summarized in a detailed and effective way, starting from Berlusconi’s mysterious beginnings (chapter two, Hur allting började) and commented with no irony, but rather with a sort of resigned incredulity.